Susceptibility test of Griseofulvin, Ketoconazole, Itraconazole, and Terbinafine to Dermatophyte Species Using Microdilution Method - Anggarini, Dyah Ratri; Sukanto, Hari; Astari, Linda; Endraswari, Pepy Dwi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Backgroud: Dermatophytosis is common disease in tropical countries such as Indonesia. The prevalence of dermatophytosis in general population also high (20%). The dermatophyte fungi are the etiologic agents that cause this disease, some of them had already reported to be resistant to some anti-fungi. Purpose: To determine dermatophyte species causing dermatophytosis and the resistancy of griseofulvin, ketoconazole, itraconazole, dan terbinafine to dermatophyte species. Methods: Isolates of dermatophyte from patient who met the inclusion criteria in outpatient clinic of dermato-venereology Dr. Soetomo Hospital Surabaya during October until December 2014 were analyzed with respect to their susceptibility to four anti-fungal agents (griseofulvin, ketoconazole, itraconazole, and terbinafine) using microdilution methode. Results: Thirthy patients were included in inclusion criteria, with T. mentagrophytes var. Interdigitale was the most common cause of dermatophytoses. According to MIC all 30 isolates were already resistant to all anti-fungal agent, except T. rubrum that still sensitive to ketoconazole and 80,Â  itraconazole.Â  Conclusion: According to MIC 16.7% isolates sensitive to griseofulvin, 23.3% to ketoconazole, 16.7% to 80 itraconazole and 20% to terbinafine.Key word: dermatophyte species, susceptibility test of anti-fungal, microdilution.